Determination of service rate and factors that affect it in intensive dairy farms of Lima, Peru - Sandoval Monzón, Rocío Silvia (2017)
This study aimed to determine the service rate (TS) in intensive dairy farms in Lima, Peru and to identify the factors affecting it. For this purpose, 144 experimental units (farm-month units) were used. Each unit consisted of 60 randomly selected cows who had more than 60 days in lactation during the study month and their conception date should be after the start date of the study month. Records of four dairy farms in the provinces of Huaura, Huaral, Lima and Cañete in the period of August 2010 to July 2013 were assessed. The effect of days in milk (DEL), production level (NPX), parity (NP), the percentage of inseminated cows by using prostaglandins (%PG), percentage of inseminated cows under fixed-time artificial insemination (%TAI) and maximum temperature-humidity index (THI Max) on service rate were evaluated. Moreover, farm, year, season and milking frequency were evaluated. TS was 44.6%. The %TAI, %THI and NP were highly significant (p<0.05), with a regression coefficient of 0.240, -0655 and -5.858 respectively. Also, the interaction year x farm and farms were highly significant (p<0.001). It is concluded that TS in the four dairy farms in Lima is below the ideal target and therefore, there is a great potential for improvement.